ULTRABASIC-BASIC INTRUSIVE VIZCAINO LAYERED COMPLEX AND VIZCAINO OPHIOLITE (SOUTHERN BAJA CALIFORNIA, MEXICO) (2008)
Two ultrabasic-basic rocks-bearing units occur in the Vizcaino Peninsula of Southern Baja California (Mexico) : the Vizcaino Layered Complex (VLC) and the San Hipolito Zone (SHZ). The VLC consists of two sequences : the lower Puerto Nuevo Sequence (serpentinite breccia, harzburgite, dunite, cyclic units), and the upper La Pintada Sequence (cyclic units, gabbros, diorites). The SHZ consists of serpentinite, actinote schists. microgabbros, spilitic pillow lavas, ophicalcites, radiolarites, tuffs, greywackes, interbedded limestone and dolomite, siliceous sandstones, and volcanosedimentary strata). The VLC is an autochtonous complex generated by a magma underplating, which is intrusive into the San Pablo Metamorphic Complex (SPMC) (amphibole-biotite gneiss with lenses of granite, migmatitic amphibolitic gneiss, orthoamphibolites). Originally, together with its metamorphic roof, the SPMC, it constituted a continental magmatic arc .The SHZ, a former Late Triassic marginal sea, is an allochthonous Carnian (?)-Norian ophiolitic unit, emplaced as a nappe upon the VLC during the Liassic. During the Late Triassic (starting at ±220 Ma) this zone underwent a long lived extensional event, during which plagiogranite dykes and dolerite/albitite dykes were emplaced into it, whereas the San Hipolito Basin opened behind it. Then, different units of the VLC were exhumed and exposed by low angle normal listric faults. It seems that the upper part of the VLC, La Pintada Sequence and the SPMC were then displaced to their present position of San Pablo-La Pintada. During the Liassic compressional phase the plagiogranite dykes were boudinaged, and slices of the SHZ Nappe came to rest upon every one of the units of the Puerto Nuevo Sequence, including the serpentinite breccia (which gave way to the erroneous notion of the so-called Puerto Nuevo Mélange of previous literature). Keywords: arc, marginal sea, magma underplating, ophiolite, Vizcaino, Baja California, tectonics